The role of ADP-ribosylation in regulating DNA interstrand crosslink repair - Gunn, A; Banos-Pinero, B; Paschke, P; Sanchez-Pulido, L; Ariza, A; Day, J; Emrich, M; Leys, D; Ponting, C; Ahel, I; Lakin, N (Company of Biologists, 2016)
ADP-ribosylation by ADP-ribosyltransferases (ARTs) has a well-established role in DNA strand break repair by promoting enrichment of repair factors at damage sites through ADP-ribose interaction domains. Here we exploit the simple eukaryote Dictyostelium to uncover a role for ADP-ribosylation in regulating DNA interstrand crosslink repair and redundancy of this pathway with non-homologous end-joining (NHEJ). In silico searches identify a protein that contains a permutated macrodomain (Aprataxin/APLF-and-PNKP-Like protein; APL). Structural analysis reveals permutated macrodomains retain features associated with ADP-ribose interactions and APL is capable of binding poly-ADP-ribose through its macrodomain. APL is enriched in chromatin in response to cisplatin, an agent that induces DNA interstrand crosslinks (ICLs). This is dependent on the macrodomain of APL, and the ART Adprt2, indicating a role for ADP-ribosylation in the cellular response to cisplatin. Although adprt2− cells are sensitive to cisplatin, ADP-ribosylation is evident in these cells due to redundant signalling by the DSB-responsive ART Adprt1a, promoting NHEJ-mediated repair. These data implicate ADP-ribosylation in DNA ICL repair and identify NHEJ can function to resolve this form of DNA damage in the absence of Adprt2.